Hv-Field of Fractions and Hv-Quotient Rings - Mansour Ghadiri (Journal of the Indonesian Mathematical Society, 2021)
A larger class of algebraic hyperstructures satisfying the ring (field)-likeaxioms is the class of Hv-rings (Hv-fields). In this paper, we define the Hv-integraldomain and introduce the Hv-field of fractions of an Hv-integral domain. Also, theHv-quotient ring and some relative theorems are presented. Finally, some interestingresults about the Hv-rings of fractions, Hv-quotient rings and the relations betweenthem are proved.